The Economics of Insurance, its Borders with Finance and Implications for Systemic Regulation - Christian Thimann (Center for Economic Studies and ifo Institute (CESifo), 2015)
Global financial regulators are currently reflecting on the nature of the insurance business. Specifically, they are trying to classify insurance into traditional' and non-traditional' activities, and to distinguish them from non-insurance' activities. Subsequently, they will seek to apply different regulatory treatments to these categories to achieve better control of systemic risk in the global financial system. This means that one of the most important current questions in international finance is what is insurance and where does insurance end?' This paper aims to elaborate on the economics of insurance and its borders with general finance. It argues that the classification challenge by regulators partly stems from terminological confusion between insurance activities and more general financial activities. Insurance and finance both use the same terms - in particular the ubiquitous notion of risk - but attach fundamentally different meanings to them. With the proper terminology at hand and a clear distinction between insurance products, product management activities and balance sheet management activities, the limits of insurance can be re-established. Such delineation is essential to determine appropriate systemic risk regulation.
Keywords: G00; G22; G28; 330; insurance economics; finance; systemic risk